Perinuclear antineutrophilic cytoplasmatic antibodies at patients with ulcerative colitis and Crohn’s disease - Ye. A. Konovich; I. A. Khalif (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Assessment of frequency and level of perinuclear antineutrophilic cytoplasmatic antibodies (pANCA) in patients with ulcerative colitis (UC) and Crohn’s disease (CD) in relation to location and spread of lesion of the large intestine, clinical activity, course of disease and applied treatment methods.Material and methods. Overall 160 patients were investigated: 104 – with UC, 36 – with CD and 20 – with irritable bowel syndrome (IBS). pANCA were determined in blood serum of patients by indirect immunofluorescence method on ethanol-fixed neutrophiles («Bio-Rad» test-system, USA).Results. pANCA have been found in 47,3, 25,0 and 5,0% of patients with UC, CD and IBS respectively (р<0,001 – UC in comparison to IBS, р<0,02 – CD in comparison to IBS, р<0,05 – UC in comparison to CD). At total, left-sided and distal forms of UC they were present in 47,7, 58,8 and 27,3% of patients respectively, at acute, chronic relapsing and chronic persistent course – in 14,3, 45,1 and 67,5% (р<0,001). In patients with severe, moderate course and in phase of remission pANCA have been revealed in 42,8, 56,0 (р<0,05) and 20,0% of cases respectively. They were found in 72,7% of patients with active total UC with chronic persistent course. pANCA titer of >1:80 was observed in 10 of 27 patients with chronic persistent course of disease and in 1 of 14 (р<0,05) with chronic recurrent course. Frequency of pANCA has tendency to increase in steroid-resistant patients and to decrease after subtotal colectomy. pANCA were found in 9 of 26 (34,6 %) patients with CD with large intestinal lesion (ileocolitis, CD of the large intestine) and were absent in 10 (p<0,01) patients with terminal ileitis. No difference between subgroups of patients with CD with high activity of process and in phase of remission was revealed.Conclusions. It was demonstrated, that at UC pANCA in greater degree are associated to diffuse lesion of the large intestine, phase of clinical activity and chronic persistent course with tendency to increase in frequency at steroid-resistant patients and to decrease after resection of affected large intestine.